2023
DOI: 10.1002/mnfr.202300472
|View full text |Cite
|
Sign up to set email alerts
|

Dietary (Poly)phenols and Cognitive Decline: A Systematic Review and Meta‐Analysis of Observational Studies

Justyna Godos,
Agnieszka Micek,
Pedro Mena
et al.

Abstract: ScopeThis study aims to systematically review observational studies investigating the relation between dietary (poly)phenol consumption and various cognitive outcomes.Methods and resultsEmbase and PubMed databases are searched from inception to April 2023 for observational studies investigating the relation between dietary (poly)phenol intake and cognitive outcomes. For quantitative analyses, random effects models, subgroup analyses, and dose–response analyses are performed. A total of 37 studies are included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Potential candidates meeting these conditions are phytochemicals, which, through regulation of normal brain function and anti-inflammatory, antioxidant, and immunostimulatory effects, influence mood and mental health [45]. Dietary polyphenols have been proven to enhance cognitive ability [24]. Numerous experimental, preclinical, and clinical studies have revealed the therapeutic antidepressant potential of various phytochemicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential candidates meeting these conditions are phytochemicals, which, through regulation of normal brain function and anti-inflammatory, antioxidant, and immunostimulatory effects, influence mood and mental health [45]. Dietary polyphenols have been proven to enhance cognitive ability [24]. Numerous experimental, preclinical, and clinical studies have revealed the therapeutic antidepressant potential of various phytochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some of them may exhibit hepatoprotective, immunosuppressive, antiplatelet, cardiovascular, antimutagenic, antiproliferative, antiangiogenic, and hypotensive activity and may also restructure the gut microbiome [22,23]. They exert a broad spectrum of biological activities that may prevent or support the treatment of many diseases [22], and the evidence from observational studies suggests that higher intakes of polyphenols may be inversely associated with the risk of cognitive disorders [24] and other chronic diseases, like cardiovascular diseases [25] and hypertension [26]. Lignans and phytosterols can have an antidepressant effect related to increasing serotonin levels, reducing cortisol levels, suppressing neuroinflammatory reactions, including in microglia, and inhibiting stressinduced damage to intestinal barrier integrity [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Most simple sugars are supposed to come from fruits. Fruits and vegetables play an important role to supply fiber, moreover are sources of minerals and vitamins, needed to avoid micronutrient deficiencies, as well as the main source of phytochemical compounds, such as (poly)phenols, that have been reported in several comprehensive summary of evidence to potentially play an important role for human health through the prevention of chronic diseases, including certain types of cancer [ 48 , 49 ], cardiovascular [ 50 , 51 ] and neurodegenerative diseases [ 52 ], and mortality [ 53 ]. While tackling malnutrition issues, some vitamins and phytochemicals may show, to a various extent, antioxidant and anti-inflammatory properties, which play a role in the prevention of non-communicable diseases [ 54 ].…”
Section: The Mediterranean Diet In Science: the Main Features In Mode...mentioning
confidence: 99%
“…Plant-derived (poly)phenols, a group of naturally occurring phytochemicals present in high amounts in fruits, vegetables and cereals, in addition to their impact on brain functions [62], have been reported to impact the intestinal microbiota by supporting the proliferation of beneficial microbes or by suppressing the proliferation of pathogens [63]. Indeed, a "prebiotic-like" effect of phenolic compounds and (poly)phenol-derived gut microbial metabolites has been reported to increase protective strains of bacteria, to decrease pathogenic inflammatory microorganisms, and to influence the Firmicutes/Bacteroidetes ratio, that is altered with ageing [17,64].…”
Section: (Poly)phenols Gut-microbiota-brain Axis and Ageingmentioning
confidence: 99%